A comprehensive study of the molecular vibrations in solid-state benzylic amide [2]catenane. Issue 35 (29th August 2019) - Romero-Muñiz, Carlos; Paredes-Roibás, Denís; Hernanz, Antonio; Gavira-Vallejo, José María
Abstract : In this work we record and assign the infrared spectrum of benzylic amide [2]catenane, a molecular solid owning mechanical bonds. By means of first-principles calculations we analyze over 1000 normal modes in terms of the usual internal coordinates. Abstract : The interpretation of vibrational spectra is often complex but a detailed knowledge of the normal modes responsible for the experimental bands provides valuable information about the molecular structure of the sample. In this work we record and assign in detail the infrared (IR) spectrum of the benzylic amide [2]catenane, a complex molecular solid displaying crimped mechanical bonds like the links of a chain. In spite of the large size of the unit cell, we calculate all the vibrational modes of the catenane crystal using quantum first-principles calculations. The activity of each mode is also evaluated using the Born effective charges approach and a theoretical spectrum is constructed for comparison purposes. We find a remarkable agreement between the calculations and the experimental results without the need to apply any further empirical correction or fitting to the eigenfrequencies. A detailed description in terms of the usual internal coordinates is provided for over 1000 normal modes. This thorough analysis allows us to perform the complete assignment of the spectrum, revealing the nature of the most active modes responsible for the IR features. Finally, we compare the obtained results with those of Raman spectroscopy, studying the effects of the rule of mutual exclusion in vibrational spectroscopy according to the different levels of molecular symmetry embedded in this mechanically interlocked molecular compound.